Managing customer satisfaction: digital applications for insurance companies - Christian Eckert; Christof Neunsinger; Katrin Osterrieder (The Geneva Papers on Risk and Insurance - Issues and Practice, 2022)
Customer satisfaction management is increasing in importance within the insurance industry. In particular, to define a customer-oriented strategy, installing digital applications based on technologies, e.g. including artificial intelligence or cloud computing, ranks among the major strategic challenges. Against this background, the aim of this paper is to take an integrated perspective on managing customer satisfaction and the digital transformation. Towards this end, we identify and assess a set of digital applications, as a result of a comprehensive review of 106 academic papers and publications of the industry and supervisory authorities. We illustrate the opportunities to increase customer satisfaction and emphasise their impact on insurers at four major customer touch points: contract conclusion, contract modifications, the event of damage and further contacts. Our results are strategic measures to strengthen the position for sales and marketing, to simplify standard processes and to increase efficiency and interaction with the customer.
Keywords: 330; Digital applications; Customer satisfaction; Insurance innovation